The Use of Tricaine Methanesulfonate (MS-222) in Asian Seabass (Lates calcarifer) at Different Temperatures: Study of Optimal Doses, Minimum Effective Concentration, Blood Biochemistry, Immersion Pharmacokinetics, and Tissue Distributions - Julia Chu-Ning Hsu; Tirawat Rairat; Yi-Ping Lu; Chi-Chung Chou (Veterinary Sciences, 2023)
This study was conducted to determine the optimal doses and minimum effective concentrations (MECs) of tricaine methanesulfonate (MS-222) in marketable-size Asian seabass reared at two temperatures (22 and 28 °C). Serum biochemical parameters, pharmacokinetics, and tissue distributions of MS-222 following immersion at the determined optimal doses were also evaluated in order to delineate possible mechanisms dictating the temperature difference. The definition of optimal dose is set as the dose when fish attain stage III anesthesia within 5 min, sustain this stage for 3 min, and re-attain equilibrium within 5 min. The MEC is the fish serum MS-222 concentration when stage III anesthesia is reached. The results showed that water temperature exerted no or minimal impact on the designated parameters. The optimal doses at 22 and 28 °C were 140 and 150 µg/mL, while the MECs were 70.48 and 78.27 µg/mL, respectively. Fish exposed to the optimal doses of MS-222 had significantly elevated blood concentrations of lactate, glucose, calcium, magnesium, and sodium, while the blood pH was significantly decreased. The fish eliminated MS-222 faster at 28 °C than at 22 °C, with serum half-lives of 18.43 and 37.01 h, respectively. Tissue-specific distribution patterns were evident. Irrespective of water temperature, MS-222 peaked at 5 min for the brain and gill but peaked slightly later at 10–20 min for the liver and kidney. Most tissues exhibit a gradual decline of drug concentration except for the gill, which was maintained at a steady level. Muscle is the least perfused tissue with the lowest drug concentration throughout the 90 min period. This study provided physiological and pharmacokinetic evidence contributing to a better understanding of the actions of MS-222 in Asian seabass at different temperatures.